Intraparotid classical and nodular lymphocyte-predominant Hodgkin lymphoma: pattern analysis with emphasis on associated lymphadenoma-like proliferations - Agaimy, Abbas; Wild, Vanessa; Maerkl, Bruno; Wachter, David; Hartmann, Arndt; Rosenwald, Andreas; Ihrler, Stephan (American Journal of Surgical Pathology, 2015)
Most of the lymphoproliferative diseases involving the salivary glands represent indolent non-Hodgkin B-cell lymphoma (marginal zone lymphoma) related to chronic autoimmune sialadenitis (Sjögren disease). Other types of non-Hodgkin lymphomas involve the salivary glands less frequently. On rare occasions, classical Hodgkin lymphoma (CHL) and nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL) present initially as a primary salivary gland mass. We analyzed a series of CHL (n=3) and NLPHL (n=6) presenting initially as parotid gland tumors concerning their pattern (parenchymal vs. intraparotid lymph node) and the presence of salivary inclusions and epithelial proliferations within the lymphoma infiltrate. The pattern of infiltration was determined on hematoxylin and eosin-stained slides assisted by immunostaining for pancytokeratin to highlight lobular salivary gland parenchyma. Patients included 6 male and 3 female individuals with a mean age of 62 years (range, 36 to 88 y). Lymphoma was localized within intraparotid lymph nodes in 8 cases and was limited to salivary parenchyma in 1 case. Parenchymal involvement in nodal-based cases was scored as absent (3) or minimal (5). Salivary inclusions (acini and ductules) within affected lymph nodes were noted in 6 cases (4/5 NLPHLs and 2/3 CHLs). In 3/6 NLPHL cases, salivary inclusions showed variable proliferative changes ranging from prominent lymphoepithelial lesions to cystic and oncocytic (Warthin-like) epithelial changes. Scanty small lymphoepithelial lesions were seen in 1 of the 3 CHL cases. One NLPHL in the intraparotid lymph node was accompanied by prominent lymphoepithelial sialadenitis in the absence of clinical signs of Sjögren disease. This study highlights that a majority of parotid gland Hodgkin lymphomas arise within intraparotid lymph nodes. Frequent entrapment and proliferation of salivary ducts and acini within the lymphoma infiltrate might mimic a variety of benign lymphoepithelial mass-forming lesions (nonsebaceous lymphadenoma, Warthin tumor, and autoimmune sialadenitis). Pancytokeratin stain is helpful for reliable assessment of the background architecture.
EVALuna2:6714